Status Hukum Perjanjian Nominee Dalam Penguasaan Tanah - Seventina Monda Devita (Widya Yuridika, 2022)
Law No. 5 of 1960 concerning the Basic Regulations on Agrarian Principles (UUPA) which is a form of protection and management in the agrarian sector, specifically in Article 21 paragraph 1 that only Indonesian citizens can own land with property rights. However, nowadays there are often nominee agreements between Indonesian citizens and foreign nationals (WNA) so that the foreigner can control land in Indonesia. So with that there is an attempt to deceive the law by foreigners to be able to fulfill their personal goals. So the author feels there is an urgency to review the legal status of the Nominee agreement from the point of view of Indonesian Civil Law. In addition to this, this writing will use a normative juridical research method with a statutory and library approach. Thus, it is hoped that it will be able to answer the legal issues that the author raises regarding efforts to deceive the law by using the Nominee agreement as a forum for foreigners to control land in Indonesia, which will find clarity on how civil law addresses this issue.